TRIK DAN STRATEGI MENINGKATKAN NILAI PRODUK MELALUI BRANDING YANG EFEKTIF UNTUK PEJUANG UMKM DESA SAWIR BERSAMA KKN TEMATIK - Nur Ma’rifati, Rr. Kusuma Dwi; Ngainin, Nurul; Gholiya, Nabila; Abdi F, Wildan (Collaborative: Jurnal Pengabdian Masyarakat, 2025)
In today’s competitive business world, branding has become a key element in differentiating products and services in the global marketplace. This article explores the importance of modern branding strategies in creating a strong and compelling product identity for consumers. We analyze the various approaches that can be used in building a brand, including the use of social media, creative visual design, effective brand narratives, and engaging customer experiences. In this article, we also review case studies from various industries that have successfully implemented successful branding strategies. We explore how elements such as brand mission, core values, and visual imagery can shape consumer perceptions and enhance competitive advantage. In addition, we discuss the positive impact of strong branding on customer loyalty, market penetration, and profit margins. Branding plays a central role in influencing consumer perceptions and preferences for products and services. This article explores the concepts and strategies of branding that contribute to marketing success. By highlighting elements such as brand identity, visual design, and brand narrative, we discuss how strong branding can differentiate products in a competitive marketplace. We also analyze the influence of social media as a critical tool in extending brand reach and engaging consumers.